Sensibilisierung photographischer Emulsionen durch Gold und die Stabilität latenter Bildkeime - W.F. Berg; O. Tanabe (CHIMIA)
Experiments are reported on the stabilization of the latent image in Ag-Br hydrosols as well as their sensitization by Au(I) and gelatine. Au(I) builds up subimage to full latent image centres. Thus the regression of subimage could be followed. Early on after exposure, it is more stable, later on less stable than the latent image, for which the specific rate of fading reaches a plateau. Sulfur-sensitization is accounted for by a topological effect: latent image is steered towards the grain surface, but is not stabilized. Gelatine will stabilize both latent and subimage centres; here and in sensitization it presumably acts as an anti-oxidant. Au(I) stabilizes small silver centres, which shows up both by sensitization and by the build-up of subimage to full latent-image centres.